Poly(Glycidyl Methacrylates)-grafted Zinc Oxide Nanowire by Surface-initiated Atom Transfer Radical Polymerization - Zhang, Bao; Hu, Nantao; Wang, Yanfang; Wang, Zi; Wang, Ying; Kong, Eric S.; Zhang, Yafei (Nano-Micro Letters, 2011)
Poly(glycidyl methacrylates) (PGMA) was grafted from zinc oxide (ZnO) nanowires via surface-initiated atom transfer radical polymerization (SI-ATRP) technique. Firstly, the ZnO nanowires were synthesized by the one-pot hydrothermal technique. Subsequently, the ZnO was functionalized with 3-aminopropyl triethoxysilane, which was converted to macroinitiator by the esterification of them with 2-bromopropionyl bromide. PGMA grafted ZnO nanowires (PGMA-ZnO) were then synthesized in an ATRP of the GMA with CuCl/2, 2`-bipyridine as the catalyst system. Kinetics studies revealed an approximate linear increase in weight of polymer with reaction time, indicating that the polymerization process owned some “living” character. The structure and composition of PGMA-ZnO were characterized with scanning electron microscope (SEM), energy-dispersive X-ray (EDX) spectrometer, fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA).